Membangun Sikap Disiplin dan Cinta Damai Siswa dalam Mencegah Perilaku Vandalisme di SDN 03 Seberang Musi Kepahiang - Buyung Wagianto; Puspa Djuwita; Abdul Muktadir (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to describe the forms of vandalism behavior, which exist in SDN 03 Seberang Musi Kepahiang, and the efforts made in building a disciplined and peace-loving attitude of students from vandalism behavior. The type of research used is qualitative with a case study approach. The subjects in this study were students as the main informants, and teachers and school caretakers as supporting informants. The instrument in this study was the researcher himself. As a key instrument the researcher made his own set of observation tools, interview guides which were used for recording during the field. The data collectors used were observation sheets, interviews, and document studies. Data analysis techniques used interactive models from Miles, Huberman, and Saldana, namely data collection, data condensation, data presentation, and drawing conclusions. The results showed that the forms of vandalism that were carried out by SDN 03 SBM students were the destruction of school facilities such as scribbling on walls, tables, chairs, breaking glass, and destroying cleaning equipment. The cause of vandalism by students at SDN 03 is because they feel bored and feel resentment or anger. Efforts were also found to build a disciplined and peace-loving attitude of students towards vandalism behavior at SDN 03 SBM, namely in the form of increasing teacher supervision, providing facilities, carrying out school and class activities, and repainting the walls. SBM is due to lack of supervision, weak self-control, solicitation of colleagues, and lack of family motivation. Apart from that, SDN 03 SBM has also made efforts to build a disciplined and peace-loving attitude towards its students.